Income Uncertainty, Customer Pressure, and Work Motivation as Drivers of Work Stress Among Online Drivers in Kendari - Ajeng Purwati Ningtyas (Universitas Dinamika, 2026)
Aims - This study addresses a gap in gig economy research within a secondary city in Eastern Indonesia by examining how income uncertainty drives work stress among online drivers in Kendari through a moderated mediation framework that integrates customer pressure as a mediator and work motivation as a buffer. Methodology - A quantitative survey design was employed. Of 130 questionnaires distributed to active Maxim and Grab drivers in Kendari City via purposive sampling, 100 were returned and deemed fully usable (76.9% response rate). Data were analyzed using PLS SEM with SmartPLS 4.0. Prior to structural model testing, common method bias was assessed using Harman's single factor test. Findings - Income uncertainty exerts a significant positive effect on work stress (β = 0.387, p < 0.001) and on customer pressure (β = 0.412, p < 0.001). Customer pressure partially mediates the uncertainty–stress relationship (indirect β = 0.123, p < 0.01), and work motivation significantly attenuates the customer pressure–stress link (β = −0.214, p < 0.01), indicating that higher motivation buffers the stress amplifying impact of demanding customers. Research Limitations - This study is limited to Maxim and Grab drivers in Kendari City, so generalization to other regions requires caution. These findings suggest that ride hailing companies need to design more stable incentive systems to reduce driver income uncertainty. Originality - This study is the first to integrate income uncertainty, customer pressure, and work motivation within a moderated mediation framework tested on gig workers in a secondary Indonesian city.